2011
DOI: 10.1007/s13213-011-0224-7
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic chromium(VI) reduction by chromium-resistant bacteria isolated from activated sludge

Abstract: A chromium-reducing strain isolated from activated sludge and subsequently identified as Clostridium sp. SS1 by a biomolecular method was studied for its resistance to toxic hexavalent chromium [Cr(VI)] and its ability to reduce Cr(IV). The strain was found to tolerate concentrations of Cr(VI) up to 50 mg/l; however, cell growth was severely affected by the presence of Cr(VI), especially at concentrations of more than 20 mg/l. Clostridium sp. SS1 also effectively reduced toxic Cr(VI) into the comparatively les… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 26 publications
0
1
0
3
Order By: Relevance
“…PerkinElmer AAnalyst 600 pada panjang gelombang 357.9 nm (Singh et al, 2013). Setelah itu dilakukan pengukuran efisiensi reduksi konsentrasi kromium oleh bakteri dengan menggunakan Persamaan 2 (Nguema & Luo, 2012).…”
Section: Identifikasi Bakteriunclassified
See 2 more Smart Citations
“…PerkinElmer AAnalyst 600 pada panjang gelombang 357.9 nm (Singh et al, 2013). Setelah itu dilakukan pengukuran efisiensi reduksi konsentrasi kromium oleh bakteri dengan menggunakan Persamaan 2 (Nguema & Luo, 2012).…”
Section: Identifikasi Bakteriunclassified
“…Berdasarkan kurva tersebut dapat diketahui bahwa penambahan kromium ke dalam media kultur dapat menghambat pertumbuhan ketiga isolat bakteri. Hasil yang sama diperoleh dari penelitian sebelumnya pada pertumbuhan Pseudomonas aeruginosa, Bacillus cereus, Ochrobactrum intermedium, Clostridium sp., Staphylococcus sp., Bacillus megaterium dan Bacillus circulans yang menunjukkan pertumbuhan bakteri yang semakin terhambat seiring dengan bertambah tingginya konsentrasi kromium dalam media kultur (Mistry et al, 2010;Munawaroh et al, 2017;Nguema & Luo, 2012;Rida et al, 2012;Singh et al, 2013;Srinath et al, 2002) (Priyadarshanee & Das, 2021).…”
Section: Hasil Dan Pembahasan Identifikasi Isolat Bakteri Laut Resist...unclassified
See 1 more Smart Citation
“…(Desai et al, 2008), and Brucella sp. (Thacker et al, 2006), Clostridium sp (Nguema and Luo, 2012), Cellulomonas sp (Field et al, 2013), have been reported to reduce Cr(VI). Bacterial reduction of Cr(VI) can be considered as a mechanism of resistance to Cr(VI) (Ohtake et al, 1997).…”
Section: Introductionmentioning
confidence: 99%